Research on Cultivation of Computer-aided Translation Talents under the Background of "Internet+". Issue 3 (October 2020) - Wang, Xiaoyi; Gao, Tingting
Abstract: In recent years, with the rapid development of language service industry, the original simple service has been far from adapting to the new development of the industry. Under the background of "Internet+", the scope of language services has expanded from simple interpretation and translation to the whole language service outsourcing, such as technical writing, website localization, multilingual information processing and other fields. Then we should start to cultivate computer-aided translation talents. At the same time, the requirements for language service practitioners are not only to master oral and written translation skills, but also to master it skills, project experience, market awareness, cross-cultural communication, professional quality, industry knowledge and localization skills, terminology management, translation technology, translation tools, typesetting and printing, translation management and other skills on this basis.